A Common Fixed Point Theorem for Strongly Tangential and Weakly Compatible Mappings Satisfying Implicit Relations: Said Beloul - Team, Support (Thai Journal of Mathematics, 2017)
this paper we prove a common fixed point theorems for two pairsof single and set valued mappings in metric space by using the strongly tangentialproperty, which satisfying implicit relations, these results generalize and improveresults of Sedghi, Altun and Shobe in their paper [11] and some previous results.